DAMPAK KURSUS KATEKIS TERHADAP PELAYANAN PARA KATEKIS - Yuanita, Elisabet Astri; Wulung, F.X. Heryatno Wono (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The main issue discussed in this research is the impact of the catechist course on the catechists' ministry in carrying out the mission of proclaiming the faith at Saint Joseph Parish, Bandung. The background of this research is based on the important role of catechists in the life of the Catholic Church as competent proclaimers of the faith, and the need for ongoing formation to support the quality of their service. This study uses a qualitative approach, with data collected through document studies, structured interviews, and Focus Group Discussions (FGD). The purpose of this research is to identify the extent to which the catechist course supports the ministry of catechists and to gain an understanding of the supporting and hindering factors in the implementation of the course at Saint Joseph Parish. The findings show that the catechist course has a positive and significant impact on enhancing spiritual maturity and understanding of the faith, especially regarding the sacraments of initiation. In addition, the course strengthens the catechists' sense of pastoral responsibility and develops catechetical skills that are relevant to the current context of the faithful. Supporting factors for the course’s effectiveness include contextualized materials, participatory learning methods, and strong community support. However, challenges remain, such as time constraints and low participation among some course participants. This research offers a meaningful contribution to the development of more effective catechist formation programs focused on sustainable empowerment and may serve as a reference for other parishes in building more contextual and impactful catechetical ministries.